Torsional vibration responses of the engine crankshaft-gearbox coupled system with misfire and breathing slant crack based on instantaneous angular speed. (1st July 2022) - Wu, Kun; Liu, Zhiwei; Ding, Qian; Gu, Fengshou; Ball, Andrew
Highlights: Torsional vibrations of the engine crankshaft-gearbox coupled system are investigated. Instantaneous Angular Speed at the flywheel and the driven shaft are compared. Natural frequencies under normal and cracked conditions are analysed in time domain. IAS at the driven shaft contains information from both the engine and the external load. The driven shaft is the better position for online monitoring sensor installation. Abstract: Torsional vibration responses of an engine crankshaft-gearbox coupled system with misfire and breathing slant crack are investigated in this paper. The crankshaft is modelled by lumped mass method and its dynamic equations are deduced based on Lagrange equation. Both the time varying mesh stiffness of the gearbox composing of a pinion and a gear and the response-dependent stiffness of a shaft element with a breathing slant crack are evaluated. Natural frequencies of the healthy and cracked systems are analysed respectively. Torsional vibrations based on the instantaneous angular speed (IAS) of the flywheel and the driven shaft are compared among the operating conditions of normal, misfire and breathing slant crack on the driven shaft. Simulation results are validated by experiments, which show that the encoder on the driven shaft is better because it can monitor the IAS of the flywheel and the driven shaft simultaneously and the signals are more prominent here.